2016
DOI: 10.1089/thy.2015.0429
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathologic Predictors of Lymph Node Metastasis and Recurrence in Papillary Thyroid Microcarcinoma

Abstract: PTMC is an indolent disease, but does pose a risk for LNM and local recurrence. More aggressive treatment or more frequent follow-up could be considered for patients with unfavorable features (age <45 years, multifocality, ETE), especially in the setting of involved lymph nodes at the time of surgical resection, as these patients may be at an increased risk for recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
109
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(133 citation statements)
references
References 25 publications
14
109
3
3
Order By: Relevance
“…Five studies were conducted in the Republic of Korea [16, 17, 21, 22, 24], one in Spain [18], five in Italy [19, 23, 25, 26, 29], one in Taiwan [20], one in United State of American [27], and one in Turkey [28]. Thirteen reports were retrospective studies [1925, 27–29], and one was prospective study [26]. The follow up durations for the recurrence of PTMC range from 2 to 24 years and the study sample sizes range from 81 to 2018 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were conducted in the Republic of Korea [16, 17, 21, 22, 24], one in Spain [18], five in Italy [19, 23, 25, 26, 29], one in Taiwan [20], one in United State of American [27], and one in Turkey [28]. Thirteen reports were retrospective studies [1925, 27–29], and one was prospective study [26]. The follow up durations for the recurrence of PTMC range from 2 to 24 years and the study sample sizes range from 81 to 2018 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Vorasubin et al (27) recently demonstrated that large, multifocal, and capsularly or lymphovascularly invasive PTMC was significantly associated with at least a 1.93 times greater risk of metastasizing than were smaller, solitary, and noninvasive tumors. Another study by Siddiqui et al (28) showed that younger age (age < 45 years), multifocality, and extrathyroidal extension were predictors of CLNM. Our data showed that male sex and tumor size were not predictive for CLNM, in contrast to findings by others (18,29,30).…”
Section: Discussionmentioning
confidence: 96%
“…In fact, AS strategy in low-risk PTMC has been suggested by a Japanese group based on single observational studies, and concerns remain about disease progression during AS, especially in patients with an aggressive phenotype 1719. Although AS has existed for approximately 10 years, it was only recently added to the international guidelines as a viable management strategy 5,14.…”
Section: Discussionmentioning
confidence: 99%